Pengelolaan Dokumen Administrasi Melalui Sistem Pencatatan Surat di Kantor Dinas Koperasi, Usaha Kecil, Menengah dan Perdagangan Kota Pematangsiantar - Sein Rezeki Tampubolon; Martin Luter Purba (PADMA, 2025)
Orderly office administration management is a fundamental aspect in supporting the effectiveness of public services and accountability in government administration. In practice, however, local government institutions often face challenges in managing administrative documents and letter recording systems, particularly those that still rely on manual procedures. This article aims to describe and analyze the role of student internships in supporting administrative document management and letter recording systems at the Office of Cooperatives, Small and Medium Enterprises, and Trade of Pematangsiantar City. The internship program was carried out by students of the Development Economics Study Program at HKBP Nommensen University within the General and Personnel Sub-Division. The methods employed included direct observation of administrative processes, assistance in recording incoming and outgoing letters using agenda and expedition books, organizing physical archives, and compiling supporting administrative documents. The results indicate improvements in the orderliness of letter recording, the neatness of archives, and the efficiency of document distribution and retrieval processes. Furthermore, the internship activities enhanced students’ practical understanding of government administrative governance. Therefore, the student internship program serves not only as an experiential learning medium but also contributes to strengthening orderly administration and supporting the operational performance of local government institutions.